PARTISIPASI CITIZEN JOURNALIST DALAM MENULIS BERITA DI KOMPASIANA.COM - Mentari Purwaningrum; Wininda Qusnul Khotimah (KAGANGA KOMUNIKA: Journal of Communication Science, 2022)
Technology increasingly developing in addition to making it easier for humans to live their lives also encourages changes in society. So far, people who have only been media consumers can now produce messages or act as journalists. Usually they are referred to as citizen journalists or citizen journalists. This study discusses Citizen Journalist Participation in News Writing at Kompasiana.com. The purpose of this study is to understand the participation of citizen journalists in writing news on Kompasiana.com. This study uses a qualitative approach and the type of descriptive research. The method used is a case study. The results of this study indicate that the participation of citizen journalists in writing news at Kompasiana.com is driven by their desire to voice their thoughts and continue to train their writing skills as an effort to self-actualize. The factors behind their participation in writing news on Kompasiana.com are their passion or interest in writing, experience factors and other supporting factors that cause people to participate, namely the existence of k-werds or gifts for writers in Kompasiana.com. The implications that are felt when involved in citizen journalism are wider knowledge and sharper and more critical analytical blades in looking at an issue, as well as being able to improve people's literacy and writing skills.